Fetal echocardiography changes of the right ventricle of well-controlled gestational diabetes mellitus - Ying Ma; XueSong Sun; XiaoZhi Liu; LiHua Hu; Ye Song; Xiong Ye (BMC Cardiovascular Disorders, 2023)
Abstract Background There is few evidence of right ventricular (RV) function in fetuses with gestational diabetes mellitus (GDM). Therefore, the aim of this study was to assess the RV function of fetuses using routine and two-dimensional speckle-tracking echocardiography (2D STE) to determine the effects of well-controlled GDM in the third trimester. Methods We used a Philips Epiq7C ultrasound instrument to obtain RV data sets from 63 subjects from July 2019 to February 2022. We compared the free wall thickness (FWT), fractional area change (FAC), Tei index (TEI), tricuspid annular plane systolic excursion (TAPSE) and free wall longitudinal strain(FWLS)of the RV in mothers with well-controlled GDM and normal gestational age-matched fetuses. Results 63 third trimester fetuses (32 GDM; 31 healthy controls) met the enrolment criteria. Significant differences in fetal RV were detected between the GDM and control groups for the FAC (36.35 ± 6.19 vs. 41.59 ± 9.11; P = 0.008) and the FWLS (-18.28 ± 4.23 vs. -20.98 ± 5.49; P = 0.021). There was a significant difference among the segmental strains of the base, middle and apex of the RV free wall in the healthy controls (P = 0.003), but in the GDM group, there was no statistical difference (p = 0.076). RV FWLS had a strong correlation with FAC (r = 0.467; P = 0.0002). Conclusions In well-controlled GDM, there was measurable fetal RV hypertrophy and significant systolic function decline, indicating the presence of ventricular remodeling and dysfunction. 2D-STE can evaluate the RV free wall contraction in a more comprehensive way.